Chondrocyte lysates activate NLRP3 inflammasome-induced pyroptosis in synovial fibroblasts to exacerbate knee synovitis by downregulating caveolin-1 - Xue Du; Ruonan Liu; Zongrui Jiang; Chengyun Zhang; Zhijian Yang; Shu Hu; Zhiqi Zhang (Arthritis Research & Therapy)
Abstract Background Synovitis, among the most common signs of early-stage osteoarthritis (OA), is mainly mediated by fibroblast-like synoviocytes (FLSs). Cartilage destruction creates chondrocyte lysates (CLs) that activate synovial inflammation. A comprehensive understanding of chondrocyte–FLS communication might offer novel, specific therapeutic targets for treating synovitis and OA. Hence, we sought to uncover the specific role of CLs in OA-FLSs and synovitis. Methods Isolated CLs were cocultured with FLSs to test whether they could stimulate synovial inflammation. A model of medial meniscus destabilization was prepared in C57BL/6 mice and NLRP3 knockout mice, and adeno-associated virus overexpressing Caveolin-1 (CAV1) was intra-articularly injected for 8 weeks once a week after dissection of the medial meniscus (DMM). Proteins expressed in FLSs with and without CL coculture were screened using liquid chromatography-tandem mass spectrometry to identify CL-specific regulators of NLRP3 inflammasome-mediated pyroptosis. Results CLs were engulfed by FLSs, which aggravated inflammatory cytokine release and NLRP3 inflammasome-mediated FLS pyroptosis. NLRP3 expression was significantly upregulated in human OA-FLSs and FLSs cocultured with CLs, while CAV1 was downregulated. CAV1 overexpression reversed the inflammatory phenotype in FLSs and simultaneously rescued pyroptosis in CL-pre-treated FLSs. Both synovial hyperplasia and inflammatory infiltration in C57BL/6 mice with DMM surgery were alleviated after intra-articular AAV-CAV1 injection. Moreover, the CL-specific protein LIM-containing lipoma preferred partner (LPP) markedly exacerbated FLS pyroptosis and inflammation. Conclusions CLs were endocytosed by FLSs through CAV1, and the CL-specific protein LPP stimulated NLRP3 inflammasome-mediated pyroptosis and synovitis by inhibiting CAV1 expression. Our findings offer a novel therapeutic target for treating synovitis.